2015
DOI: 10.1380/ejssnt.2015.256
|View full text |Cite
|
Sign up to set email alerts
|

Phase Coexistence in Two-Dimensional Fe<sub>0</sub><i><sub>.</sub></i><sub>70</sub>Ni<sub>0</sub><i><sub>.</sub></i><sub>30 </sub>Films on W(110)

Abstract: Using low energy electron microscopy, diffraction and x-ray photoemission electron microscopy, we study the phase separation in an Fe-Ni alloy film on W(110) at around 30 at.%Ni and at monolayer thickness. At high temperature, the monolayer-thick alloy is shown to transform into a biphase with submicron regions of different surface density exhibiting (1 × 1) and (1 × 8) structures. The former is pseudomorphic to the bcc substrate, whereas the latter is a slightly-distorted hexagonal adlayer lattice reminiscent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 18 publications
(21 reference statements)
0
1
0
Order By: Relevance
“…At the limit of ultrathin films, the presence and the nature of phase separation was addressed in a recent work on a Fe 0.70 Ni 0.30 monolayer on W(110). 13 It was shown that the alloy monolayer decomposes into bcc (pseudomorphic) and fcc-like (hexagonal) monolayer regions. The Ni content in the bcc and fcc-like regions were measured to be x = 0.15 and x = 0.42, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…At the limit of ultrathin films, the presence and the nature of phase separation was addressed in a recent work on a Fe 0.70 Ni 0.30 monolayer on W(110). 13 It was shown that the alloy monolayer decomposes into bcc (pseudomorphic) and fcc-like (hexagonal) monolayer regions. The Ni content in the bcc and fcc-like regions were measured to be x = 0.15 and x = 0.42, respectively.…”
Section: Introductionmentioning
confidence: 99%